2015
DOI: 10.1364/oe.23.027405
|View full text |Cite
|
Sign up to set email alerts
|

2-LP mode few-mode fiber amplifier employing ring-core erbium-doped fiber

Abstract: A fiber amplifier supporting 2 LP modes that employs a ring-core erbium-doped fiber (RC-EDF) is investigated to reduce differential modal gain (DMG). The inner and outer radii of the ring-core of the RC-EDF are clarified for 2-LP mode operation of the amplifier, and are optimized to reduce the DMG. It is shown that using the overlap integral between the erbium-doped core area and the signal power mode distribution is a good way to optimize the inner and outer radii of the ring-core of the RC-EDF and thus minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…We chose 980 nm LP 01 pumping, because we have assumed that the pumping light source of this EDF is the same LP 01 mode output LD as the conventional EDFA, and it is possible to perform more efficient pumping than the higher order modes that require mode conversion such as a phase plate. The erbium ions emission and absorption crosssections, and the signal/pump background losses we used are the same as those described by Ono et al [6] and Yamada et al [7]. Fig.…”
Section: Rc-edf Structure and Numerical Simulation Method: Figs 1a Amentioning
confidence: 99%
See 2 more Smart Citations
“…We chose 980 nm LP 01 pumping, because we have assumed that the pumping light source of this EDF is the same LP 01 mode output LD as the conventional EDFA, and it is possible to perform more efficient pumping than the higher order modes that require mode conversion such as a phase plate. The erbium ions emission and absorption crosssections, and the signal/pump background losses we used are the same as those described by Ono et al [6] and Yamada et al [7]. Fig.…”
Section: Rc-edf Structure and Numerical Simulation Method: Figs 1a Amentioning
confidence: 99%
“…The erbium ions emission and absorption cross‐sections, and the signal/pump background losses we used are the same as those described by Ono et al . [6] and Yamada et al . [7].…”
Section: Rc‐edf Structure and Numerical Simulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RI profiles of the RCFs: The RI profile will also affect the DMG performance of the core-pumped RCF-EDFAs. H. Ono et al analysed how the combinations of the inner and outer radius of the SI-RCF affected the DMG of their 2-LP-mode RCF-based EDFAs and reported that low DMG could be achieved by adopting the inner radius of about 2.5-4 μm and the outer radius near the LP21 cut-off values [81,82]. Based on simulation [77] and experimental [76] results, Y. Jung et al showed that lower DMG of the EDFA could be achieved by utilizing GI-RCF under core-pumped operation without severe micro-bending, compared with that of the SI-RCF EDFA with large differential RI between core and cladding [78].…”
Section: A Rcf-based Erbium Doped Fibre Amplifiers (Edfas)mentioning
confidence: 99%
“…Recently we have theoretically proposed a FM-RC-EDFA capable of providing almost identical gain among six mode groups within the C-band using either core-or claddingpumped implementations [6]. In reference [7], the first ring-core fibre (RCF) amplifier supporting two mode groups (LP01 and LP11) has been demonstrated and a small DMG of around 1dB was realized.…”
Section: Introductionmentioning
confidence: 99%